2008
DOI: 10.1111/j.1471-4159.2008.05659.x
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms for recycling and biosynthesis of endogenous cannabinoids anandamide and 2‐arachidonylglycerol

Abstract: Abbreviations used: 2-AG, 2-arachidonyl glycerol; D 9 -THC, delta-9-tetrahydrocannabinol; AEA, arachidonylethanolamine (anandamide); AM404, N-(4-hydroxyphenyl)-Arachidonylamide; ARA, arachidonic acid; BSA, bovine serum albumin; CAD, Cath.a differentiated; FAAH, fatty acid amide hydrolase; KRH, Kreb-Ringer Hepes; NAPE PLD, N-acyl phosphatidylethanolamine phospholipase D; SOCE, store-operated calcium entry. AbstractThe mechanisms of endogenous cannabinoid biosynthesis are not completely understood. We hypothesiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 48 publications
1
30
0
Order By: Relevance
“…To label the CAD cells, the tritiated precursor was added to the medium where it could be incorporated into the cells. Previously, we observed that the tritiated precursors (AEA or ArA) could be taken up into the cognate mast cell line RBL-2H3, metabolized, and then reincorporated into membrane phospholipids to be recycled into new endocannabinoids (AEA or 2-AG)(Placzek et al, 2008). The question was whether a similar phenomenon could be observed for the neuronal CAD cells.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…To label the CAD cells, the tritiated precursor was added to the medium where it could be incorporated into the cells. Previously, we observed that the tritiated precursors (AEA or ArA) could be taken up into the cognate mast cell line RBL-2H3, metabolized, and then reincorporated into membrane phospholipids to be recycled into new endocannabinoids (AEA or 2-AG)(Placzek et al, 2008). The question was whether a similar phenomenon could be observed for the neuronal CAD cells.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, we have previously observed that these treatments deplete membrane cholesterol in CAD cells (McFarland et al, 2008). There is growing evidence linking endocannabinoid signaling and lipid rafts (Bari et al, 2005; Maccarrone et al, 2009; Rimmerman et al, 2008; Szoke et al ,2010) and specifically evidence supporting that endocannabinoid synthesis and release occurs at or near caveolae (Placzek et al, 2008; McFarland and Barker, 2005; McFarland et al, 2004; McFarland et al, 2008; Rimmerman et al, 2008). Therefore, the effects of the disruption of caveolae on OAG-induced endocannabinoid biosynthesis and release were assessed.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nonetheless, eCBs and CB 1 Rs are co-localized in lipid rafts (Barnett-Norris et al 2005, Placzek et al 2008a), and sphingosine and sphinganine would be present in these microdomains where they could potentially act as endogenous CB 1 R antagonists. Moreover, S1P can regulate its own production from sphingosine through S1PR-induced increases in SphK activity (Meyer zu Heringdorf et al 2001).…”
Section: Exogenous Ligandsmentioning
confidence: 99%